Empowering Women to Understand Their Role as the Prime Builder of Inclusive Society - Badrah Uyuni (AJIS: Academic Journal of Islamic Studies, 2018)
The inclusive society is the condition where all people fell valued. Their differences are respected, and their basic needs are met so they can live in dignity. There are many ways to achieve this dream to become true in society. One of the best ways is to acknowledge woman’ roles as the prime part of the society. As women build half of society and responsible for the nurturing, guidance and reformation of the generations of both men and women. When the women as the first teachers do not have a strong foundation in their own divine identity, we are distorted our beliefs about relationships and our own world, and when it could be accommodated this so called inclusive society. In fact, they are often at a disadvantage condition due to many factors which are rooted in the society. There are some steps that have been done to increase women's dignity by the Government, society, non-governmental organizations and the like. And it is considered successfully develop the life style of most people from the outlook of the education, economic, health, politics and others. However, there is missing link that should be existed on these improvements. The consciousness and the awareness of the women responsibility for her to developing their authentic identity is should be recognized not only by them, but also by the community in general. The family, the society and the Government in general should accommodate their existence, and never ending awareness to be always mature in building the inclusive society